2018
DOI: 10.3390/nu10070948
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Aronia, Red Ginseng, Shiitake Mushroom and Nattokinase Potentiated Insulin Secretion and Reduced Insulin Resistance with Improving Gut Microbiome Dysbiosis in Insulin Deficient Type 2 Diabetic Rats

Abstract: The combination of freeze-dried aronia, red ginseng, ultraviolet-irradiated shiitake mushroom and nattokinase (AGM; 3.4:4.1:2.4:0.1) was examined to evaluate its effects on insulin resistance, insulin secretion and the gut microbiome in a non-obese type 2 diabetic animal model. Pancreatectomized (Px) rats were provided high fat diets supplemented with either (1) 0.5 g AGM (AGM-L), (2) 1 g AGM (AGM-H), (3) 1 g dextrin (control), or (4) 1 g dextrin with 120 mg metformin (positive-control) per kg body weight for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Importantly, we found that supplementation of dietary L. Edodes β-glucan prevented this shift in microbiota composition, as it signi cantly increased Bacteroides and decreased Firmicutes. Consistent with our ndings, two previous studies have shown a similar capability of L. Edodes β-glucan to alleviate the gut microbiome dysbiosis in aged mice and insulin de cient type 2 diabetic rats [18,19]. In addition, it has been reported that microbiota belonging to the phylum Bacteroidetes is associated with cognition and neurodegenerative diseases [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, we found that supplementation of dietary L. Edodes β-glucan prevented this shift in microbiota composition, as it signi cantly increased Bacteroides and decreased Firmicutes. Consistent with our ndings, two previous studies have shown a similar capability of L. Edodes β-glucan to alleviate the gut microbiome dysbiosis in aged mice and insulin de cient type 2 diabetic rats [18,19]. In addition, it has been reported that microbiota belonging to the phylum Bacteroidetes is associated with cognition and neurodegenerative diseases [35].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that L. edodes can be used medicinally for diseases involving hyperlipidemia, hypertension and diabetes [17]. Interestingly, two studies have reported that the supplementation of L. edodes derived β-glucan for consecutive 28 days can improve gut microbiome dysbiosis in aged mice [18], and thereby improve insulin resistance in insulin-de cient type 2 diabetic rats [19]. Moreover, a recent cross-sectional study has shown that mushroom consumption had reduced the incidence rate of mild cognitive impairment in aged individuals in Singapore [20].…”
Section: Introductionmentioning
confidence: 99%
“…A report demonstrated that pumpkin polysaccharide had the ability to ease the phenotype of T2D in rat model induced by high-fat diet and streptozotocin and selectively enriched the butyric acid–producing microbiota in rat gut, which is the potential mechanism ( Liu et al, 2018 ). In a non-obese type 2 diabetic animal model, the pancreatectomized rats were provided diets supplemented with aronia, red ginseng, shiitake mushroom, and nattokinase (AGM) ( Yang et al, 2018 ). After 12 weeks’ feed, the experimental group showed enhanced insulin secretion and reduced insulin resistance, as well as improved the gut microbiome dysbiosis.…”
Section: Diet With Genetics Epigenetics and Metagenomics Involved Imentioning
confidence: 99%
“…Furthermore, even Asians with normal BMIs are susceptible to T2DM [21]. Partially pancreatectomized rats have an insulin secretion capacity of 50-60% and islet numbers at 40-50% of normal [22,23], and are not obese. Accordingly, we chose this model to represent T2DM in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Dried cocoon hydrolysates of silkworms (Bombyx mori L.) were provided by Worldway Co. Ltd. (Sejong, Korea) and stored at −20 • C. Hydrolysates were prepared by washing the cocoons in 13-15 volumes of water and reacting with 2N HCl at 100-110 • C for 12 h. Acid hydrolyzed peptides were filtered and desalted to <0.3% at pH 5.5-7.5. Hydrolysates were then sterilized, concentrated to [20][21][22][23][24][25] Brix by low-pressure evaporation, and spray dried. Amino acid contents of silk peptides (SPs) were measured using an amino acid analyzer (L-8500; Hitachi, Tokyo, Japan), as described previously [5].…”
Section: Acid Hydrolyzed Silk Peptides (Sps)mentioning
confidence: 99%